PROBLEMS ENCOUNTERED IN THE TRANSLATION OF DRAMATIC WORKS - Omonova Shakhlo Sirojiddinovna ,; Javliyev Mansurbek Odil o’g’li , (TADQIQOTLAR.UZ, 2023)
Abstract: This article examines the changes that occur in the process of translation of English-Uzbek, Uzbek-English interlanguage dramatic works, and the types and problems of translating dramatic works and preserving the meaning in them. In the process of translating dramatic works, it is important to transfer them to the original text language and the translation language. Solutions for correct implementation of the translation while preserving the original content of the texts are offered.